FLOUTING MAXIM AND HEDGING MAXIM IN MULTICULTURAL STUDENTS INTERACTION - Maya Rizki Amalyasari; Ima Widiyanah (Journey: Journal of English Language and Pedagogy, 2019)
IKIP Budi Utomo as a private campus in the city of Malang has a composition of students from various tribes and cultures, making it a campus with a multi-cultural society. On this campus there are five tribes that dominate, they are: Javanese, Madurese, Dayaks, Sumba Flores, and Ambon. In multicultural societies, there are often obstacles, which in turn cause conflicts, in communication. A convention is needed between the speaker and the hearers so that communication becomes effective and efficient, and is able to minimize misunderstandings. In this case the concept called the principle of cooperation (Cooperative Principles) which is intended as a rule of communication in order to run effectively and efficiently becomes relevant to be studied. The design of this study is descriptive qualitative in which data sources obtained from dialogs that arise in daily interactions both between multicultural students and students and lecturers inside and outside the class at IKIP Budi Utomo Malang. In line with the results of the research analysis, it can be concluded that, of the 476 utterances recorded as raw data of this study, there were 45 cases of maxims flouts and 12 cases of maxims hedges, which formed a certain pattern in each multicultural students.